ASSOCIATION BETWEEN THE ORGANIZATION AND ENVIRONMENTAL FACTORS AND WORK INJURIES AMONG HOME HEALTH CARE NURSES - Abdulkhaleq, Sania Mohammed; Griffin, Harold Ray; Gutierrez, Mary Lou (LIFE: International Journal of Health and Life-Sciences, 2018)
Work-related injuries have an adverse impact on health and safety of the employees, patients, and health care organization. Nurses’ exposure to work injuries is one of the highest rates in home and community care institutions. Nurses working in home health care (HHC) encounter multidimensional risk factors, including the organizational and environmental hazards associated with HHC. The purpose of this cross-sectional study was to examine the relationship between the organization and environmental factors and the work injuries (WIs) as experienced by HHC nurses (HHCNs). A prediction of the significant factors related to work injuries was explored. A self-reported data was obtained from 74 nurses working in nine HHC units in the Makkah Region, KS, using the Safety Home Care Nursing (SHCN) questionnaire. The results showed that the supervisory support (SS) (β = -0.36, p = .009) and the access to a client's home (AC) (β = -0.25, p= 0.05) were negatively affecting the WIs as experience by HHCNs. This implies that the training of Front-line supervisors and HHC providers in safety management and safety communication would improve competence in effective implementation of safety practices. This study suggests to ensure a safe HHC through the execution of an integrative approach involving managers, nurses, and other practitioners, as well as the patients’ and their informal caregivers.